Trend Analysis of Ship Accidents in Indonesia - Faturachman, Danny; Shariman, Mustafa (2012)
There are so many accident in sea transportation in Indonesia. Accidents occurring in rivers, lakes, and crossing that reached Marine Court in 2005-2010 is due to human error factor (88%), and only a few accidents in the waters caused by natural factors. Given the reasons mentioned above should all accidents can be minimized if prevention efforts from all parties so as not to stumble on the same stone. Water transport accidents occur mainly due to overcrowding and navigation system, which is characterized by a large number of passengers and goods compared to the draft Commission. For passengers who do not have the expertise and skills in emergency situations, it is important to note that users of the waterway into the category of vulnerable population groups (vulnerable). Efforts to ensure the safety of passengers and crew must be a serious problem, especially in this trivial security equipment, such as buoys. Current conditions, many ships that do not have safety equipment that should buoy passengers and crew when the vessel hit the accidents. Most of the accidents occur due to the low awareness of the aspects of security and safety of the crew. The figures differ from the manifest of passengers and number of passengers on the ground become commonplace. There are four main issues in maritime transport, it is said, not the individual agencies or Government willing to hold responsibility for the security and safety, pricing policy, the quality of human resources, as well as the implementation and compliance with the rules are not clear.